2012
DOI: 10.3892/or.2012.1998
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated receptor-2 induces expression of vascular endothelial growth factor and cyclooxygenase-2 via the mitogen-activated protein kinase pathway in gastric cancer cells

Abstract: Protease-activated receptor-2 (PAR-2) has shown strong pro-angiogenesis activity physiologically and pathologically. This study aimed to explore PAR-2 regulation of pro-angiogenesis gene expression and the underlying molecular pathways in gastric cancer cells. MKN28 human gastric cancer cells were treated with trypsin, a PAR-2 activator, and subjected to real-time reverse transcription polymerase chain reaction (qRT-PCR), western blotting and ELISA for gene expression analyses. ERK1/2 phosphorylation and p38 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…PAR-2 expression/activation has been described in a number of human epithelial malignancies [14, 15, 34] and triggers growth factor/chemokine release from malignant cells, including IL-6 [14], IL-8 [12], and VEGF [13]. PAR-2 activation in EOC may similarly impact the peritoneal microenvironment [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR-2 expression/activation has been described in a number of human epithelial malignancies [14, 15, 34] and triggers growth factor/chemokine release from malignant cells, including IL-6 [14], IL-8 [12], and VEGF [13]. PAR-2 activation in EOC may similarly impact the peritoneal microenvironment [35].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, PAR-2 signaling is associated with a promigratory, invasive, and proangiogenic phenotype in experimental models of breast cancer [1113]. PAR-2 activation and induction of growth factor/chemokine expression, including prominently vascular endothelial growth factor (VEGF), has been described in renal cell carcinoma and colon cancer cell lines [14, 15]. Thus, the TF/FVIIa/PAR-2 axis may directly contribute to the progression of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Tryptase is an agonist of PAR-2 in vascular ECs that stimulates their proliferation. Signaling via PAR-2 on ECs elicits activation of the major members of the MAPK phosphorylation family and contributes to proliferation of ECs and angiogenesis [23,24,25,26,27,28,29,30,31,32,47,48,49,50,51]. …”
Section: Discussionmentioning
confidence: 99%
“…So far, few data have been published on the relationship among MCs density positive to tryptase (MCDPT), and microvascular density (MVD) in both primary gastric cancer (GC) tissue and loco-regional lymph node metastases (LRLNM) [6,28,29,30,31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…3), a potent angiogenic factor, by these cells (Chang et al, 2013;Dutra-Oliveira et al, 2012;Liu and Mueller, 2006;Zhang et al, 2012). Furthermore, these studies reported that activation of PAR 2 by either trypsin or PAR 2 -activating peptides resulted in signalling via a number of pathways, including PI3K-dependent Akt pathways and ERK1/2 and p38 MAPK pathways.…”
Section: Par 2 Signalling and Tumour Angiogenesismentioning
confidence: 96%